Protective effects of melatonin, vitamin E and N-acetylcysteine against acetaminophen toxicity in mice: a comparative study - ŞENER, GÖKSEL (My University, 2003)
Acetaminophen (AA) is a commonly used analgesic and antipyretic drug; however, when used in high doses, it causes fulminant hepatic necrosis and nephrotoxic effects in both humans and experimental animals. It has been reported that the toxic effects of AA are the result of oxidative reactions that take place during its metabolism. In this study we investigated if melatonin, vitamin E or N-acetylcysteine (NAC) are protective against AA toxicity in mice. The doses of the antioxidants used were as follows: melatonin (10 mg/kg), vitamin E (30 mg/kg) and NAC (150 mg/kg). Blood urea nitrogen (BUN), serum creatinine, alanine aminotransferase (ALT), aspartate aminotransferase (AST) levels in blood, and glutathione (GSH), malondialdehyde (MDA), oxidized protein levels and myeloperoxidase (MPO) activity in liver and kidney tissues were measured. BUN and serum creatinine, ALT and AST levels which were increased significantly following AA treatment decreased significantly after pretreatment with either vitamin E, melatonin or NAC; however, they were not reduced to control levels. ALT and AST levels were significantly higher at 4 hr compared with the 24 hr levels after AA administration. However, BUN and creatinine levels were significantly elevated only at 24 hr. GSH levels were reduced while MDA, MPO and oxidized protein levels were increased significantly following AA administration. These changes were reversed by pretreatment with either melatonin, vitamin E or NAC. Liver toxicity was higher at 4 hr, whereas nephrotoxicity appeared to be more severe 24 hr after treatment with AA. Vitamin E was the least efficient agent in reversing AA toxicity while melatonin, considering it was given as at lower dose than either vitamin E or NAC, was the most effective. This may be the result of the higher efficacy of melatonin in scavenging various free radicals and also because of its ability in stimulating the antioxidant enzymes.
Keywords: Animals; Melatonin; Liver; Vitamin E; Blood Urea Nitrogen; Creatinine; Kidney; Acetaminophen; Analgesics, Non-Narcotic; Mice; Acetylcysteine